Why don't we talk about meaning at work meaningful work will remain elusive if managers don't learn to overcome four barriers to healthy conversations about what gives individuals their sense of purpose - Lips-Wiersma, Marjolein; Bailey, Catherine; Madden, Adrian; Morris, Lani (MIT Sloan Management Review, 2022)
The more employers try to tell employees where to find the meaning in their work, the less likely people are to find it. An authentic sense of purpose is discovered, not imposed, so meaning-making should be a grassroots process. But first, managers and employees must learn how to talk with one another about it. Research shows that four barriers make such conversations difficult. Here's how to overcome them in your organization.
Reprint #63407, Summer 2022 issue, vol. 63, no. 4. - Includes bibliographical references
Keywords: Employee motivation; Leadership; Meaning (Psychology); Personnel; Motivation; Signification (Psychologie)